2011
DOI: 10.5483/bmbrep.2011.44.9.584
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of SAV1 by mammalian ste20-like kinase promotes cell death

Abstract: The mammalian ste20-like kinase (MST) pathway is important in the regulation of apoptosis and cell cycle and emerges as a novel tumor suppressor pathway. MST-induced phosphorylation of Salvador homolog 1 (SAV1), which is a scaffold protein, has not been evaluated in detail. We performed a mass spectrometric analysis of the SAV1 protein that was co-expressed with MST2. Phosphorylation was detected at Thr-26, Ser-27, Ser-36 and Ser-269. Although single or double mutations had little effects, the mutation of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Coexpression of Hippo with Sav or Lats results in the phosphorylation of both, whereas expression of all three further enhances Lats (but not Sav) phosphorylation, as visualized by electrophoretic slowing; the Hippo and Sav SARAH domains are required for this effect[11]. Similar responses are reported with coexpression of WW45, Lats1 and Mst2 [57,71]. The impact of WW45 on the regulation of Mst1 and Lats1/2 in more physiologic conditions was examined in mouse primary embryonic keratinocytes, which can be induced to differentiate by addition of Ca ++ at mM levels.…”
Section: The “Hippo” Kinases Hippo Mst1 and Mst2mentioning
confidence: 79%
“…Coexpression of Hippo with Sav or Lats results in the phosphorylation of both, whereas expression of all three further enhances Lats (but not Sav) phosphorylation, as visualized by electrophoretic slowing; the Hippo and Sav SARAH domains are required for this effect[11]. Similar responses are reported with coexpression of WW45, Lats1 and Mst2 [57,71]. The impact of WW45 on the regulation of Mst1 and Lats1/2 in more physiologic conditions was examined in mouse primary embryonic keratinocytes, which can be induced to differentiate by addition of Ca ++ at mM levels.…”
Section: The “Hippo” Kinases Hippo Mst1 and Mst2mentioning
confidence: 79%
“…Since Sav ubiquitylation occurs in the C-terminal domain responsible for Hpo binding, Hpo could sterically interfere with ubiquitin ligase binding or ubiquitin transfer. Alternatively, since Hpo is known to phosphorylate Sav ([ 7 , 9 , 45 , 46 , 51 ] and this report), phosphorylation might prevent ligase binding or ubiquitylation. To investigate these possible mechanisms, we analysed the effect of several Hpo truncations and mutants on Sav ubiquitylation ( Fig 3 A ).…”
Section: Resultsmentioning
confidence: 87%
“…This result suggested that the core members of the Hippo pathway, comprising at least one of the upstream Ste-20 kinases (STK4 and STK3), SAV1 and LATS1 as well as MOB2 molecule might form a larger and more complex functional compound in which SAV1 serves as a connector to assembly them together through a mode of action similar to the previously reported in mammals [ 47 ]. Furthermore, the SAV1 molecule was reported to have several phosphorylation residues that were phosphorylated by MST in human [ 33 , 34 , 35 ]. In this study, we found that chicken SAV1 was also phosphorylated by SKT4 or SKT3 kinase of the Hippo/MST pathway in the GCs of the developing ovarian follicles, and the phosphorylated SAV1 was able to significantly enhance the phosphorylation levels of LATS1 induced by the kinase of STK4 or STK3 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the phosphorylation of chicken SAV1 mediated by the Ser/Thr protein kinase STK4 or STK3 may be most important in the regulation of oocyte maturation and granular cell proliferation during ovarian follicle growth by the Hippo/MST pathway. As for whether the detailed phosphorylated residues within the chicken SAV1 is consistent to those having been determined in mammals [ 35 ], further studies will be required to address this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation